Intrahousehold Allocation of Free and Purchased Mosquito Nets - Hoffmann, Vivian (American Economic Review, 2009)
For some health goods, intrahousehold allocation may be more important in determining outcomes than household-level consumption. An example is the use of mosquito nets to prevent malaria. Malaria kills over one million people annually, 90 percent of them children under the age of five. The use of insecticide treated mosquito nets (ITNs) is considered the most costeffective available strategy for control of the disease. In 2000, 44 of the 50 malaria affected countries in Africa committed themselves to increasing the use of ITNs by vulnerable populations, in particular children under five years of age and pregnant women. Adults in malarious regions have typically acquired some immunity to the disease through repeated exposure over the course of their lives. The risk of severe malaria resulting in lifelong disability or death is highest for young children and pregnant women across transmission environments (Robert W. Snow et al. 2003). On the other hand, lost labor time often accounts for the largest portion of the private cost of the disease. This implies a trade-off between minimizing the income lost to malaria and minimizing the risk that a household member dies or is permanently disabled. Despite public health messages emphasizing the importance of using mosquito nets to protect young children from malaria, nets are often used by adults when a household does not have enough nets to cover all members (Eline L. Korenromp et al. 2003; Frederick Mugisha and Jacqueline Arinaitwe 2003). Determining the welfare-maximizing allocation of nets is Intrahousehold Allocation of Free and Purchased Mosquito Nets